2002
DOI: 10.1017/s0022112002008509
|View full text |Cite
|
Sign up to set email alerts
|

Laminar flow past a sphere rotating in the streamwise direction

Abstract: Numerical simulations are conducted for laminar flow past a sphere rotating in the streamwise direction, in order to investigate the effect of the rotation on the characteristics of flow over the sphere. The Reynolds numbers considered are Re = 100, 250 and 300 based on the free-stream velocity and sphere diameter, and the rotational speeds are in the range of 0 [les ] ω* [les ] 1, where ω* is the maximum azimuthal velocity on the sphere surface normalized by the free-stream velocity. At ω* = 0 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
65
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 17 publications
17
65
0
2
Order By: Relevance
“…Although this régime is periodic and the flow fields would be steady in a frame rotating at ω x around the z-axis, these vorticity fields closely resemble those prevailing in the quasiperiodic régime (see figure 7) and are rather different from those of the low-frequency helical régime (see figure 5). It is as if the axial vortex shedding and the helical "solid-body" rotation were locked together, or "frozen" (Kim and Choi, 2002).…”
Section: High-frequency Helical Régimementioning
confidence: 99%
See 1 more Smart Citation
“…Although this régime is periodic and the flow fields would be steady in a frame rotating at ω x around the z-axis, these vorticity fields closely resemble those prevailing in the quasiperiodic régime (see figure 7) and are rather different from those of the low-frequency helical régime (see figure 5). It is as if the axial vortex shedding and the helical "solid-body" rotation were locked together, or "frozen" (Kim and Choi, 2002).…”
Section: High-frequency Helical Régimementioning
confidence: 99%
“…The efficiency of this model relies, among other things, on the fact that the leading eigenmodes have very similar growth rates, favouring (weak) nonlinear interactions which control the complex bifurcation scenario. Inspired by these findings, the present investigation revisits the configuration used by Kim and Choi (2002): the wake of a sphere rotating about a streamwise oriented axis. The rotation of the sphere introduces a chirality in the problem but does not break the axisymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Two special directions of sphere rotating are usually taken to be representative ones, which are the streamwise rotation and the transverse rotation. Some work has been carried out to investigate the relation between the rotational speed and the force exerted on the sphere both for the cases of transverse rotation [14][15][16][17][18] and streamwise rotation [19][20][21] of the sphere. Schlichting [19] has summarized the previous results of ow over a streamwisely rotating sphere.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that as the rotating speed of the sphere increased, the rotating e ects got stronger and the vortex shedding under the e ect of body rotation resulted in a swirling vortex structure in the near wake. Recently, another numerical simulation of viscous ow past a sphere rotating in the streamwise direction was conducted by Kim and Choi [21].…”
Section: Introductionmentioning
confidence: 99%
“…In figure 7, we present the comparison in terms of drag coefficient C D between the results calculated by means of IBLGF and those by Kim & Choi, 20 for both the non-rotating and rotating sphere. The initial transient that can be observed for the IBLGF curves is due to the impulsive initialization of the simulations.…”
Section: Iva Flow Past a Non-moving Axisymmetric Bluff Bodymentioning
confidence: 99%